Determinant Factors of Fruit and Vegetable Consumption in Rural and Urban Adolescents Jakarta (Social Cognitive Theory Approach) - Adhila Fayasari; Tri Ardianti Khasanah (Journal of Nutrition Science, 2025)
Fruit and vegetable consumption in Indonesia still does not meet the recommended levels. Low intake of vegetables and fruits poses a risk of cardiovascular disease and mortality. Adolescence is a critical period for instilling healthy behaviors before transitioning into adulthood. The aim of this study is to analyze the factors influencing vegetable and fruit consumption among adolescents in rural and urban areas of Jakarta. The study used a cross-sectional design conducted in urban and semi-rural areas of Jakarta with a two-stage cluster sampling technique. Data related to knowledge, attitudes, preferences, self-efficacy, social, economic, and environmental factors, as well as family and peer behavior, were collected using questionnaires. Data on vegetable and fruit intake were collected using the SQ-FFQ. The data were analyzed using chi-square and logistic regression analysis with α < 5%. The determinants of vegetable and fruit consumption among adolescents in rural areas were parental influence and peer influence, while in urban areas, the determinants were parental influence and vegetable preferences. A tailored approach based on environmental and social characteristics is needed to promote healthy eating behaviors among adolescents.